Awareness, Enrollment and Utilization of Health Insurance among Adults of Pokhara - Sharma, Dibya; Basnet, Priyanka; Kafle, Ramchandra (Journal of College of Medical Sciences-Nepal, 2021)
Introduction Procuring a health insurance is important because medical care is expensive, especially in private sector. Hospitalization nowadays is very expensive. Financial burden while being sick can be managed wisely by paying a small annual premium which would lessen stress in case of medical emergencies. The objective of study is to assess awareness, enrollment and utilization of health insurance and find out association between awareness and enrollment with demographic variables. Material and methods A descriptive cross sectional study was conducted to assess awareness, enrollment and utilization of health insurance among adult of Phulbari-11, Pokhara. The study was conducted during the period from June – August 2019 among 153 adult using purposive sampling. The data was analyzed using descriptive and inferential statistics using Statistical Package for Social Science(SPSS) version 18.0. Result: Nearly 61% were young adult. About 2/3rd (66%) were female. Majority (82.4%) had received some form of formal education. About 57% were aware about health insurance and 40% had enrolled in it. Among them, more than 2/3rd (69%) had procured service at least once. Respondent's awareness is statistically significant with ethnicity. Enrollment in health insurance is significantly associated with age, ethnicity, marital status, history of chronic illness, family history of chronic illness and awareness of health insurance. Conclusion: Awareness about health insurance is low. Enrollment and utilization of the scheme is not as expected. The enrollment in this scheme can further be enhanced through government effort to increase awareness among community people with the help of health care personnel and media.